Climate Change and Inpatient Dermatology - Fathy, R. (Curr Dermatol Rep, 2020)
PURPOSE OF REVIEW: Climate change represents a major existential threat facing the global community, and it has already begun to affect human health in a multitude of ways. This review highlights and discusses the implications that climate change has already had and is expected to have for inpatient dermatologists. RECENT FINDINGS: There are a variety of conditions affected by climate changes. The distribution and frequencies of infectious diseases and their vectors are changing in line with variations in climate conditions. Increased temperatures have already been associated with exacerbation of existing skin conditions, such as atopic dermatitis, and recent evidence suggests that higher temperatures will also magnify the effects of harmful ultraviolet radiation. Extreme weather events that result from climate change are followed by an array of dermatologic conditions that may be unusual for the given location. Inpatient dermatologists should be prepared to manage these potentially unfamiliar dermatologic consequences of climate change. SUMMARY: Climate change will have widespread effects on the medical field, and inpatient dermatologists will be faced with their own unique set of challenges and practice variations. Practitioners should be familiar with the ongoing and predicted effects of climate change in their locations so that they can readily identify and treat associated conditions, and they should adjust their practice to reduce their carbon footprint and serve as a model for patients to do the same.